PREFACE - Mohd Azlan, Jayasilan; Mohamad Irwan, Aman; Indraneil, Das (UNIMAS Publisher, Sarawak Energy Berhad and Natural History Publications (Borneo) Sdn. Bhd., 2024)
Sarawak is located in one of the world’s mega diversity regions, and boasts an array of Bornean endemic species, from plants to large mammals, some of which are only found in the State. Some of these species are considered the world’s rarest and most threatened, being distributed in the remotest of habitats.